2013
DOI: 10.1055/s-0033-1335857
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Contrast-Enhanced Ultrasound (CEUS) in the Detection of Metastatic Superficial Lymph Nodes in Melanoma Patients

Abstract: CEUS increases the diagnostic accuracy of US in the differential diagnosis of benign and malignant LNs but it also allows us, when possible, to avoid unnecessary invasive operations such as LN FNAC. Moreover, CEUS may guide FNAC in the case of focal cortical thickening on the basis of hypoperfusion, with a reduction in the number of false negatives and much earlier detection of nodal metastatic foci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 13 publications
0
16
0
3
Order By: Relevance
“…Non‐invasive techniques such as MR‐spectroscopy, PET/MRI, high‐frequency ultrasound, ultrasound‐based elastography, contrast‐enhanced US, power and colour Doppler US, perfusion US, multimodality imaging systems, and photoacoustic imaging have been used for detection and management of various cancers, including skin cancer. Ultrasound modalities are a particularly attractive option because they are widely available, quick, relatively inexpensive, easy to use, and have the potential to guide pretreatment planning, and provide real‐time imaging during biopsy and surgery .…”
Section: Resultsmentioning
confidence: 99%
“…Non‐invasive techniques such as MR‐spectroscopy, PET/MRI, high‐frequency ultrasound, ultrasound‐based elastography, contrast‐enhanced US, power and colour Doppler US, perfusion US, multimodality imaging systems, and photoacoustic imaging have been used for detection and management of various cancers, including skin cancer. Ultrasound modalities are a particularly attractive option because they are widely available, quick, relatively inexpensive, easy to use, and have the potential to guide pretreatment planning, and provide real‐time imaging during biopsy and surgery .…”
Section: Resultsmentioning
confidence: 99%
“…36 A large study on 540 patients with melanoma implementing CEUS for superficial lymph node metastases was conducted by Rubaltelli et al in 2014. 37 The authors concluded that after i.v. delivery of microbubbles, the node enhancement pattern interpretation increases the diagnostic accuracy of ultrasound in the differential diagnosis of benign and malignant lymph nodes by up to 0.99 and helps avoid unnecessary fine needle biopsy.…”
Section: Resultsmentioning
confidence: 99%
“…Initial evidence for a potential benefi t of contrast-enhanced ultrasound was reported by Rubaltelli and coworkers in a population of 540 patients with malignant melanoma. Compared to fi ne needle aspiration as the standard of reference, the authors observed a sensitivity of 100 % and a specifi city of 99.5 % for contrast-enhanced ultrasound in the detection of lymph node metastases [ 65 ].…”
Section: Ultrasound Assessment Of Lymph Nodesmentioning
confidence: 98%